Some strange substrates for macrofungi in the Pampa Biome - Brazil - Putzke, Jair; Falcão, Marina de Souza; Furlan-Lopes, Cassiane; Costa, Alice Lemos; Silva, Fernando Augusto Bertazzo; Mueller, Guilherme Henrique; Velloso, Jorge Renato Pinheiro (Revista Ambientale, 2024)
Macrofungi usually are found growing on vegetal substrate, soil or dung, but sometimes they have the opportunity to explore some very unusual food. Studying mushrooms in São Gabriel municipality, southern Brazil (Pampa Biome) allow us to collect specimens in different substrata rarely or still not reported in the literature. The collections include Amanita muscaria subsp. flavivolvata growing in Eucalyptus plantation, Clitopilus argentinus growing on a wasp nest, Cheimonophyllum candidissimum growing on rock, Marasmius neosessilis on the shrub Asparagus officinalis (Angiosperm) and Panaeolina foenisecii in Capibara dung. The implications of such ecological relationship are discussed. To Clitopilus a review of the species reported to Brazil is presented.